YEARS OF WORLD WAR II ACTIVITIES OF HISTORIANS IN UZBEKISTAN - Муминов А. Г; Эрназаров Ш. Э. (TARIXIY TADQIQOTLAR, 2025)
This article will be devoted to the joint scientific research work of historians in the Uzbek SSR during the Second World War and their role and role in revealing unknown pages of the history of these years.